IMPLEMENTASI APLIKASI ARDUINO IDE PADA MATA KULIAH SISTEM DIGITAL - Kamal; Firdayanti; Ulfa Mahaning Tyas; Andi Apri Buckhari; Pattasang (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
Learning can be interpreted as a set of plans or patterns that can be used to design learning materials and guide learning activities as a systematic procedure in organizing learning experiences to achieve learning goals. Efforts offered by researchers to improve student learning outcomes by implementing the Arduino IDE application. This study aims to find out how the process of implementing the Arduino Idea application and student learning outcomes in the Digital Systems course, Informatics Engineering Study Program, Faculty of Engineering, Islamic University of Makassar. This research is a quasi-experimental research. The total population is 60 people and the entire population is used as a sample. Based on the results of the control class pretest (A1) and the experimental class (A2), the average student learning outcomes were still low as well as the posttest results of the control class (A1) student scores in the incomplete category were 56% and only 44% completed while in the experimental class ( A2) with the application of the Arduino Ide application there was an increase in student learning outcomes in the unfinished category of 26% and 74% complete. This indicates an increase in student learning outcomes with the Arduino IDE application.